THE EFFECT OF USING RUBBER SEED WASTE ON K-300 COMPRESSIVE STRENGTH TEST (f’c 25 MPa) - MUHAMMAD JAMALUDIN; GALI PRIBADI; LYDIA DARMIYANTI (CV KULTURA DIGITAL MEDIA, 2024)
Modern construction technology has evolved with the principle of environmental concern through various innovations that support environmentally friendly construction. This includes the use of natural materials, procedures that minimize the use of hazardous resources, and techniques that produce minimal waste. The industry is also faced with the challenge of increasing demand for building materials due to population growth, which is addressed by utilizing local resources and waste, such as rubber seed shells as an alternative to conventional materials. The history of rubber use in Indonesia began with the introduction of seeds by Henry A. Wickham in 1876, with further development in the late 19th century. Based on the results of the research that has been conducted and the discussion in the previous chapter regarding the variation of the use of rubber seed shell waste of 0%, 5%, and 10%, the following conclusions can be drawn: The results of the ordinary concrete compressive strength test at the age of 28 days reached 440 kN (fc'24.91 Mpa), while variation 1 of 5% rubber seed waste reached 317 kN (fc' 17.95 Mpa), and variation 2 of 10% rubber seed waste reached 274 kN (fc'15.51 Mpa).